Citicoline for the Management of Patients with Traumatic Brain Injury in the Acute Phase: A Systematic Review and Meta-Analysis - Julio José Secades; Helmut Trimmel; Byron Salazar; José Antonio González (Life, 2023)
Background: Citicoline or CDP-choline is a neuroprotective/neurorestorative drug used in several countries for the treatment of traumatic brain injury (TBI). Since the publication of the controversial COBRIT, the use of citicoline has been questioned in this indication, so it was considered necessary to undertake a systematic review and meta-analysis to evaluate whether citicoline is effective in the treatment of patients with TBI. Methods: A systematic search was performed on OVID-Medline, EMBASE, Google Scholar, the Cochrane Central Register of Controlled Trials, ClinicalTrials.gov, and Ferrer databases, from inception to January 2021, to identify all published, unconfounded, comparative clinical trials of citicoline in the acute phase of head-injured patients— that is, treatment started during the first 24 h. We selected studies on complicated mild, moderate, and severe head-injured patients according to the score of the Glasgow Coma Scale (GCS). The primary efficacy measure was independence at the end of the scheduled clinical trial follow-up. Results: In total, 11 clinical studies enrolling 2771 patients were identified by the end. Under the random-effects model, treatment with citicoline was associated with a significantly higher rate of independence (RR, 1.18; 95% CI = 1.05–1.33; I2, 42.6%). The dose of citicoline or the administration route had no effect on outcomes. Additionally, no significant effects on mortality were found, and no safety concerns were noticed. Conclusions: This meta-analysis indicates some beneficial effects of citicoline’s increasing the number of independent patients with TBI. The most important limitation of our meta-analysis was the presumed heterogeneity of the studies included. Registration: PROSPERO CRD42021238998